Fibre waviness characterisation and modelling by Filtered Canny Misalignment Analysis (FCMA). (1st March 2023) - Qi, Songming; Alajarmeh, Omar; Shelley, Tristan; Schubel, Peter; Rendle-Short, Kendric; Zeng, Xuesen
Graphical abstract: Highlights: Capture and quantify the waviness and fibre misalignment in reinforced composites including in-plane and out-of-plane waviness. Improve the computational efficiency and increase the precision of fibre identification. The image analysis result was used as input to Finite Element (FE) modelling to quantify the effect of fibre waviness on the compressive strength of the full-scale columns. Abstract: Accurate and cost-effective full-scale measurement of fibre waviness and misalignment in continuous fibre-reinforced composite structures remains a challenge. This study proposes a novel approach of Filtered Canny Misalignment Analysis (FCMA) to capture and quantify in-plane and out-of-plane fibre waviness. The FCMA method measures fibre misalignment from the microscope and Charge Couple Device scan images by a Canny edge detector and a Canny edge filter to effectively identify the true fibre path. The method is systematically evaluated and benchmarked with the existing High Resolution Misalignment Analysis (HRMA) method. The results show that the FCMA method is more robust, efficient, and precise for fibre waviness measurements. The fibre misalignment in selected hollow composite columns is quantified by the FCMA method. The in-plane waviness distribution is used as a material orientation input to a verified finite element model. This simulation demonstrates the effect of fibre waviness on stress distribution for a hollow composite column under axial compression. The FCMA method code is supplied as supplementary material to this paper.